Endotoxinas nas infecções endodônticas: revisão sistemática com metanálise e ensaio clínico randomizado - Rabello, Diego Guilherme Dias de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Sabe-se que as endotoxinas provenientes das bactérias grã-negativas desempenham um importante papel nas infecções endodônticas se relacionando à sinais e sintomas clínicos/radiográficos. Sendo assim, a redução ou eliminação de endotoxinas é fundamental para a resolução da inflamação periapical. Os objetivos do presente estudo foram: Artigo 1 - realizar uma revisão sistemática com metanálise com o intuito de avaliar a relação entre níveis de endotoxinas e a presença de sinais e sintomas clínicos, bem como de sinais radiográficos em pacientes com infecção endodôntica primária; Artigo 2 - fazer um ensaio clínico randomizado para avaliarmos estratégias clínicas para otimizar a eliminação microbianana e de lipopolissacarídeos (LPS) utilizando a Terapia Fotodinâmica (PDT) como tratamento suplementar ao PQM nas modalidades de terapia endodôntica em única e múltiplas sessões. Métodos: Artigo 1 - para a revisão sistemática uma busca eletrônica foi realizada por dois autores, no idioma inglês, nas bases de dados Medline/PubMed, Embase, Cochrane Library, Scielo, Science Direct, Web of Knowledge e Scopus. Após seleção dos artigos foi realizado uma metanálise com análises de sinais e sintomas clínicos/radiográficos. Artigo 2 - Selecionou-se 24 casos de dentes com infecção endodôntica primária que foram aleatoriamente divididos em 2 grupos (n=12): SU - sessão única e SM – sessão múltipla. Foram realizadas coletas microbiológica e de endotoxinas dos canais radiculares utilizando cone de papel estéril/ apirogênico em diferentes momentos operatórios. Foi realizado cultura microbiana para determinar a carga bacteriana em UFC/mL (Unidades Formadoras de Colônias/mL) e para quantificação de endotoxinas foi realizado o teste KQCL de “Lisado de Amebócito Limulus” (LAL). Resultados: Artigo 1 - A metanálise revelou que individuos com dor à percussão (TTP) (P=0,04; I2 57%) e episódio de dor prévio (PEP) (P=0,001; I2 81%) apresentaram maior nível de endotoxina que os casos que não apresentaram nenhum destes sintomas. O tamanho da área radiolucente (SRL) > 2 mm (P=0,02; I2 68%) e presença de exudação (EX) (P=0,0007; I2 0%) estavam associados com maior nível de endotoxinas. Artigo 2 - Para carga microbiana, a suplementação do tratamento em sessão única com PDT reduziu significativamente os níveis bacterianos (p<0,05), mas não nos casos de duas sessões (p>0,05). Para os níveis de endotoxinas, na sessão única e de duas sessões, não houve diferença significativa após uso de PDT (p>0,05). Foi possível concluir que Artigo 1 – A metanálise mostrou forte evidência que endotoxina está relacionada com a presence de sinais e sintomas clínicos/radiográficos em pacientes com infecção endodôntica. Artigo 2 - A terapia fotodinâmica melhorou o desempenho da desinfecção bacteriana dos canais radiculares em uma visita, mas não para a modadilidade de 2 visitas após uso de medicação à base de Ca(OH)2. PDT não foi efetivo contra endotoxinas.

Endotoxins originating from gram negatives bacterias are related to signals and clinical/radiographic symptoms. Therefore, reduction or elimination of endotoxins is essential to solve periapical inflammation. The aim of this dissertation was: Article 1 - To relate endotoxin levels and presence of clinical signs/symptoms and radiographic features in endodontic infection. Article 2 - To evaluate the effectiveness of supplemental photodynamic therapy (PDT) in optimizing the removal of bacteria and endotoxins from primarily infected root canals after one-visit and two-visit treatments. Methodology: Article 1 - Electronic searches were performed on Medline/PubMed, Embase, Cochrane Library, Scielo, Science Direct, Web of Knowledge and Scopus databases for identification of relevant studies published up to July 2016. Only reports in English were included. The selected literature was reviewed by two authors and classified as either suitable or unsuitable for inclusion in this review. The relationship between endotoxin levels and presence of clinical signs/symptoms and radiographic features were determined. Additionally, a meta-analysis was performed. Article 2 - 24 primarily infected root canals with apical periodontitis were selected and randomly divided into one-visit (n=12) and two-visit (n=12). Samples were collected before and after root canal procedures. Endotoxins were quantified by chromogenic limulus amebocyte lysate assay. Culture techniques were used to determine bacterial colony-forming unit counts. The systematic review and meta-analysis aimed to evaluate the relationship between endotoxin levels and presence of clinical signs/symptoms and radiographic features in patients with endodontic infection. Results: Article 1 - Among the 285 articles identified in the initial search, 29 were included for full-text appraisal and only eight studies met the inclusion criteria for this systematic review. Meta-analysis revealed that individuals having teeth with tenderness to percussion (TTP) (P=0.04; I2 57%) and previous episode of pain (PEP) (P=0.001; I2 81%) had higher levels of endotoxin than their counterparts. Size of radiographic lesion (SRL) > 2 mm (P=0.02; I2 68%) and presence of root canal exudation (EX) (P=0.0007; I2 0%) were associated with higher levels of endotoxin. Article 2 - Bacteria and endotoxins were detected in 100% of the initial samples, with median values of 1.97 x 105 CFU/mL and 24.983 EU/mL, respectively. The CMP using single-file reciprocating technique was effective in the reduction of bacteria and endotoxins (All, p < .05). The supplemental PDT was effective in reducing bacterial load in the one-visit (p < .05) but not in the two-visit treatment after use of Ca(OH)2 medication for 14 days (p>.05). In the two-visit group, after 14 days of inter- appointment medication with Ca(OH)2, a significant reduction in the median levels of endotoxins was found in comparison to CMP alone (from 1.041 to 0.094 EU/mL)(p < .05). Despite the type of treatment, the supplemental PDT was not effective against endotoxins (p>.05). Conclusion: Article 1 - This meta-analysis provides strong evidence that endotoxin are related with the presence of clinical signs/symptoms and radiographic features in patients with endodontic infection. Article 2 - The photodynamic therapy optimized the disinfection of bacteria from root canals in one-visit but not for two visit treatment modality with the accomplishment of calcium hydroxide medication. Thus, PDT is not effective against endotoxins.
Endotoxins in endodontic infection: a systematic review with meta-analysis and a randomized clinical trial
Keywords: Periodontite periapical; Tratamento do canal radicular; Desinfecção; Endotoxina; Revisão sistemática; Metanálise; Bacterial reduction; Disinfection; Endodontic treatment; PDT; Photodynamic therapy; Endotoxins; Systematic review; Meta-analysis